Effect of PEM on thyroid status, serum total protein and A/G ratio in pre-school going children - Sah, Sumesh Prasad; Arora, Manisha; Kumar, Sudeep; Batra, Jyoti; Mustafa, Imran; Yadav, Lalendra (International Journal of Research in Medical Sciences, 2017)
Objective: The objective of the study was to evaluate and compare serum total protein, serum albumin and thyroid hormones in children with Protein Energy Malnutrition (PEM) and in healthy controls. Methods: Present study was a cross sectional hospital based case control study, total 75 children of age group 1-5 years were included in this study. Triiodothyronine (T3), thyroxine (T4) and thyroid stimulating hormone (TSH) was estimated by electro-chemiluminescence immunoassay method, serum total protein by biuret method, albumin by BCG method and plasma hemoglobin by CMG method. Result: In malnourished children, there is significant decrease in serum total protein (4.76 gm %), albumin (2.24 gm %) and Hb (10.57 gm %) as compared to normal healthy children. Serum T3 (0.51 ng/ml), and T4 (3.93 µg/ml) levels were significantly decreased and non-significant changes in TSH (4.26 µUI/ml) levels in children with PEM was observed as compared to healthy controls. Conclusion: The reduction in protein is due to decreased intake of proteins and reduced biosynthesis. The decreased in T3 and T4 levels in malnourished children is probably due to a decrease in circulating plasma proteins.